Pengaruh Employer Attractiveness dan Motivasi Kerja dengan Keterampilan Digital sebagai Variabel Intervening terhadap Kinerja Karyawan - Widiyarti , Retno; Indiworo , Rr. Hawik Ervina; Violinda , Qristin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of employer attractiveness and work motivation on employee performance, with digital skills as a mediating variable in the furniture industry in Jepara. The research is driven by the need for digital adaptation in traditional industries and the observed underutilization of digital facilities by employees. A quantitative approach was employed using a survey method. Data were collected through questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The variables examined include employer attractiveness, work motivation, digital skills, and employee performance. The results indicate that both employer attractiveness and work motivation significantly influence employee performance, either directly or indirectly through digital skills. Digital skills act as an effective mediating variable that strengthens the relationships among the variables. This research offers practical insights for companies to formulate human resource development strategies that align with technological advancements to enhance overall performance.